Valoración económica del servicio de secuestro de CO2 en dos tipos de bosque de los ríos Cochiquinas y Yavari, Ramón Castilla Loreto Perú 2021 - Espíritu Pezantes, Jorge Miguel (2021)
The Amazonian forests are considered one of the world’s largest carbon sinks, however, little information exists on the economic value of the CO2 sequestration environmental service offered by the forest species of different types of forest. This information is important to negotiate the service in the carbon market and achieve the sustainable use of the forest resource. The economic value of the CO2 sequestration offered by the tree species of the low-terrace forest of the Cochiquinas river and the low-hill forest of the Yavarí river, Loreto, was quantified in this study. The forest census database of all existing commercial species in both forests was used. The results indicate that the low-terrace forest contributes an economic value of CO2 sequestration of USD 19 771,19/ha and the low hill forest contributes an economic value of USD 15 015,83/ha. The species with the highest contribution in the low-terrace forest are Eschweilera grandiflora and Virola loretensis and in the low-hill forest are Eschweilera coriacea and Virola elongata. No significant statistical difference (? = 0,05) between the economic values per hectare of CO2 sequestration were found in both types of forest; therefore, it is recommended to insert in the carbon market the CO2 sequestration service offered by these forests as an alternative for non-destructive and sustainable use of the forest.